Discussing the Notion of Decent Work: Senses of Working for a Group of Brazilian Workers without College Education - Ribeiro, Marcelo A.; Silva, Fabiano F.; Figueiredo, Paula M. (Frontiers in Psychology, 2016)
Despite recent stability and socioeconomic development, Brazil’s history is marked by social inequality, informality, precarious work and psychosocial vulnerability, with little opportunity for decent and meaningful work, as recommended by the International Labour Office (ILO), for people in the country. Nevertheless, based on a social constructionist view, the hypothesis can be raised that there is no substantive definition of decent work, but rather a psychosocial one, constructed based on the discourse, narratives and practices produced through the relational processes which grant sense and meaning to work. Therefore, the examination of narratives and discourses is an important methodological strategy to understand the socio-occupational reality of Brazil. Thus, this study aims to understand the senses attributed to working through content analysis of the narratives produced by a set of 20 urban workers and contrast them with the ILO definition of decent work, in an effort to analyze the relationships, similarities and differences between an established collective social discourse and the interviewees’ singular narratives. The main results point out that the participants look for working with fair wages, social protection, safety, and personal development opportunities, as the ILO recommends. The main difference is that these characteristics do not derive from the State’s actions, as in the employment and formal qualification model, but come from informal sources, such as family and community relationship networks. The informal relationship networks produce job opportunities as well as social protection; qualification takes place through practical learning from more experienced colleagues; the opportunity to be able to keep working (employed or working informally) leads to success and safety; and the possibility to make choices and have control over one’s life translates into personal and occupational development. In conclusion, the participants searched for working according to the principles recommended by the ILO. Nevertheless, in contexts of vulnerability and with restricted support from the State, these principles are constructed in the community and not offered by the public power, which generates distinguished forms of decent work.